TO QUESTION OF PROVIDING QUALITY OF EDUCATIONAL PROCESS IN FUTURE PHYSICIANS PREPARING: RELATIONSHIP BETWEEN THE TEACHER AND STUDENT - Крупновицька, І. Г.; Сабадош, Р. В.; Крупновицька-Сабадош, М. Ю.; Данилюк, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
High education reforms and health care create the need for a society in highly educated professionals, which, in its turn, raises the requirements for teaching staff. The article presents the importance of the relationship between teachers and students in the learning of medical disciplines and their influence on the formation of a students' personality, on the training of professionals of high quality, which is extremely important in the context of reforming health care and high education in Ukraine. From the first steps of future medical workers training in the process of modern studies students must learn the culture of medical work, defined by such components as professional (medical) activity and communication with the patient. All this is provided by the tutor, who teaches the students both being professionals and having the ability to speak and deal with patients, forming up a student as a doctor. The main person in the pedagogical process is a competent and experienced teacher. He should not only give knowledge and skills of his narrow specialty, but also have psychology knowledge, such as methods of psychological influence on the student. In the article the emphasis is placed on the technological development of students’ teaching and the influence of students on the development of pedagogical culture and skills of the teacher. Surely, modern technology helps both the student and the teacher to interact better, but only a live communication with the tutor helps to distribute time rationally, to plan the process of learning and mastering the material correctly. Pedagogical skills in modern conditions of introduction of new initial technologies requires dynamic and qualitative growth of the teacher, non-standard approaches to teaching, improvement of methodical provision of pedagogical process.